Jus Gentium & the Arab as Muselmänner: The “Islamist Winter” is the Pre-Emptive (Creative) Chaos of the “Arab Spring” Multiplying Necropolises - Al-Kassimi, Khaled (My University, 2020)
While the (re)conquest of Arabia as manifest in 2003 Iraq, and 2006 Lebanon, were respectively Act I and II accenting sovereign figures exercising necropower by adjudicating (il)legal doctrines (i.e., pre-emptive defense strategy) legalizing extrajudicial techniques of violence founded on discursive technologies of racism, I argue that the “Islamist Winter” – temporarily dubbed the “Arab Spring” in 2011 – is Act III reifying similar legal doctrines (i.e., Bethlehem Legal Principles) and a (secular) linear temporal perception of time seeking to implement a New Middle East (NME) that is no longer “resistant to Latin-European modernity” but amenable to such inclusive exclusion historicist telos. The importance of “creative anarchy” as a positivist legal technique in producing chaotic developments such as carnage and a “crisis” or “emergency” of displacement – with sovereign members of jus gentium authorizing agents of terror (i.e., death squads/war-machines) – is that it reveals the deadly technologies of racism and relations of enmity inherent in sovereignty as a positivist juridical concept endowing sovereign figures with the power to formulate legal doctrines that ultimately subjugate Arab life to the power of death (necropower). Therefore, one of the main questions orbiting the writing of this dissertation is interested in deconstructing and critiquing jus gentium – by adopting a Third World Approach to International Law (TWAIL) in tandem with necropolitics and biopolitics as paradigms of analysis – to disclose that it is because jus gentium valorizes positivist jurisprudent scholastics postulating an unbridgeable cultural gap between an Athenian mode of Being as a universal sovereign subject, and a Madīnian mode of Being as the particular object denied sovereignty, that leads ratiocinative sovereign figures to legally exercise necropower on the Arab body. Therefore, the following chapters seek to go beyond the limited (post-colonial) idea asserting that the problem with international law is that it is primarily “Eurocentric” since the simple solution to such a claim would be to include the non-European body in International Law. Rather, the primary question constellating this monograph is: what are the experienced consequences of being temporally included and what are the experienced consequences of being temporally excluded from a legal regime (i.e., jus gentium) reifying a Latin-European philosophical theology universalizing a particular set of liberal-secular cultural mores as a “cultural benchmark” (i.e., purity-metric) in order to be-come imagined as temporally “inside” jus gentium?
JUS GENTIUM & THE ARAB AS MUSELMÄNNER
Keywords: Jus gentium; International law; Positivist jurisprudence; Necropolitics; Biopolitics; Displacement; Operation Timber sycamore; Arab Spring; Islamist Winter; Constructive Chaos; Regional Refugee Resilience Program (3RP); Homo Sacer/Musulmann; Arab Philosophical Theology; Latin-European Philosophical Theology